Information Disclosure According to International Accounting Regulation and its Impact on the Length of Financial Statement of the Capital Groups Listed on the WSE - Prewysz-Kwinto, Piotr; Voss, Grażyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The changes in economic reality have a direct impact on accounting standards, which adopting to these changes, require entities to disclose more and more information. This causes an increase in the length of financial statement, but at the same time does not necessarily translate into an improvement in their quality and usability. This paper presents the most important aspects of disclosure in financial statement based on international accounting regulations and main problems related to this process. The results of the own study on disclosure in financial statement of the largest capital group listed on the Warsaw Stock Exchange and their impact on the length of prepared financial statements, were also presented and constitute the most important part of this paper.